Using stable isotopes in deciphering climate changes from travertine deposits: the case of the Lapis Tiburtinus succession (Acque Albule Basin, Tivoli, Central Italy) - Mancini, Alessandro; Cornacchia, Irene; Lamal, Joachim; Capezzuoli, Enrico; Swennen, Rudy; Brandano, Marco (Frontiers in Earth Science, 2024)
The deposition of the Lapis Tiburtinus travertine succession occurred during the Late Pleistocene (150-30 ka) and coeval with the last activity of the Colli Albani volcanic complex. Two boreholes (Sn1 and Sn2) were drilled in the Acque Albule Basin, crossing the entire Lapis Tiburtinus succession. The Sn1 borehole, performed in the central part of the basin, crosscuts a travertine succession of 62.1 m in thickness, while the Sn2 borehole, performed in the southern part of the basin, is characterized by a travertine succession of 36.3 m in thickness. Carbon and oxygen stable isotope ratios were analysed on 118 samples (59 samples both for Sn1 and Sn2 boreholes), representative of the entire Lapis Tiburtinus travertine succession crossed by the boreholes. Values, measured and correlated in the two drilled boreholes, permit to identify the sensitivity to glacial and interglacial cycles of the travertine depositional system, unravelling the complex oxygen and carbon cycle dynamic recorded in such sedimentary succession. Moreover, the obtained results, correlated with available pollen curves of Mediterranean area (i.e., Castiglione crater), regional and global oxygen isotope continental and marine curves and calibrated with the stratigraphy of the Acque Albule Basin and the available U/Th dating, allow to identify at least 3 phases of the last interglacial (Marine Isotope Stage 5-MIS5). The carbon isotope record, compared with CO2 flux reconstructed and associated to the volcanic activity of Colli Albani volcanic complex, shows instead an influence of groundwater level changes. In particular, positive shifts, occurred during arid phases, are associated to a lower groundwater level and an increased CO2 degassing, inducing a major fractionation effect on carbon isotopes. Instead, the negative shifts occurred during more humid periods indicate the inhibition of CO2 degassing and increase in pressure, attesting a rise in groundwater level. In this view, travertine deposits, frequently studied to define the tectonic setting and activity of the area where they develop, thus potentially can also be used as a tool to understand climate changes and groundwater variations testified in their stable oxygen and carbon isotope signature.